Effectiveness of the novel ventilation system for airborne particle reduction in ambulance - Rojanasarntikul, Dhanadol; Phuchortham, Phorjai; Lerthirunvibul, Nichapa (Chulalongkorn Medical Journal, 2024)
Background: During the coronavirus disease 2019 pandemic, emergency medical service (EMS) workers are exposed to infectious particles in closed spaces such as in the ambulances. Few studies have demonstrated the effectiveness of ambulance ventilation systems in reducing airborne particles. Objectives: To evaluate the efficacy of a proposed ventilation system for use in ambulances in decreasing the volume concentration of airborne particulates and the return to background time. Methods: Aerosol particles of varying sizes were administered into the cabin by saline nebulization for 1 min. The aerosol volume concentrations of particles at 0.5 - 1.0, 1 - 2.5, and 2.5 - 5.0 microns were measured with three ventilation settings (switched off, medium and maximum) at three seat positions (front, side, and rear). Results: The return-to-background time was significantly different among the three ventilation settings (P < 0.001). Regardless of the particle size, the return-to-background times were 815 (IQR790 - 840), 830 (IQR790 - 840), and 790 seconds (IQR760 - 810) seconds for the switched off ventilation setting at the front, side, and rear seats, respectively. At all three seat positions, the return to background time for the medium ventilation setting was 360 (IQR360 - 360) seconds. For the maximum ventilation setting, the return-tobackground time were 285 (IQR280 - 290), 295 (IQR290 - 300), and 300 (IQR290 - 300) seconds at the front, side, and rear positions, respectively. Conclusion: Clearance of airborne particles is increased at higher ventilation setting. Installation of this system in the ambulance cabin may provide better control of aerosol particle suspension and will minimize the risk of airborne transmission among ambulance workers.